2000
DOI: 10.1037/0096-1523.26.2.758
|View full text |Cite
|
Sign up to set email alerts
|

Syllables in the processing of spoken Italian.

Abstract: Five experiments explored the role of the syllable in the processing of spoken Italian. According to the syllabic hypothesis, the sublexical unit used by speakers of Romance languages to segment speech and access the lexicon is the syllable. However, languages with different degrees of acoustic-phonetic transparency give rise to syllabic effects that vary in robustness. It follows from this account that speakers of phonologically similar languages should behave in a similar way. By exploiting the similarities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
65
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 37 publications
9
65
1
Order By: Relevance
“…This finding adds to a growing body of research that suggests that fine-grained subphonemic information in the speech signal can modulate lexical activation, both in the recognition of individual words (Andruski, Blumstein, & Burton, 1994;Dahan, Magnuson, Tanenhaus, & Hogan, 2001;Marslen-Wilson & Warren, 1994;McQueen, Norris, & Cutler, 1999) and in the recognition of words in continuous speech (Gow, 2002;Gow & Gordon, 1995;Spinelli, McQueen, & Cutler, 2003;Tabossi et al, 2000). Our results are also consistent with Davis et al (2002), who showed that subphonemic cues can be used to resolve ambiguities caused by lexical embedding.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This finding adds to a growing body of research that suggests that fine-grained subphonemic information in the speech signal can modulate lexical activation, both in the recognition of individual words (Andruski, Blumstein, & Burton, 1994;Dahan, Magnuson, Tanenhaus, & Hogan, 2001;Marslen-Wilson & Warren, 1994;McQueen, Norris, & Cutler, 1999) and in the recognition of words in continuous speech (Gow, 2002;Gow & Gordon, 1995;Spinelli, McQueen, & Cutler, 2003;Tabossi et al, 2000). Our results are also consistent with Davis et al (2002), who showed that subphonemic cues can be used to resolve ambiguities caused by lexical embedding.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, listeners have been shown to use the acoustic cues to syllabic structure that are available in the speech signal to favor the candidate words that match that syllabic structure (Tabossi, Collina, Mazzetti, & Zoppello, 2000). In a study that is more directly related to the problem of lexical embedding, Quené (1992) used ambiguous two-word sequences such as the Dutch phrases diep in and die pin and showed that Dutch listeners make use of variations in the intervocalic-consonant duration to assign a syllabic structure, and, as is the case in his stimuli, a word boundary.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, using the attentional allocation technique introduced by Pitt andSamuel (1990), Pallier, Sebastián-Gallés, Felguera, Christophe, andMehler (1993) examined the effect of a manipulation of listeners' expectations. They showed that phoneme monitoring was facilitated when participants were induced to expect targets in a fixed position within the syllabic structure (i.e., either at the coda as in tactile or at the onset as in tableau), regardless of their absolute phonemic position (for example, in the ''onset'' case, caprice as well as problème; see also Tabossi, Collina, Mazetti, & Zoppello, 2000, for similar results in Italian).…”
mentioning
confidence: 92%
“…However, none of them constitutes direct evidence in favor of the hypothesis that the syllable serves as an access code to the mental lexicon. While Tabossi et al's (2000) But first-part responses split nearly evenly between CV and CVC responses (e.g., ballon Ͼ ba or bal). Moreover, the tendency to produce closed (CVC) first-part responses was more manifest for more sonorous consonants and also was influenced by orthographic gemination (e.g., ballon vs palais).…”
mentioning
confidence: 99%
“…Parallel activation has also been found for embedded words (e.g., bone in trombone facilitates recognition of the semantically related rib 2 and words that are spanning a word boundary. 4 More recently, the eye-tracking paradigm has been used to demonstrate this core process of spoken-word recognition: when being presented with a display of objects, listeners take longer to look at a target object mentioned in an utterance when the display includes objects with similar names (e.g., later looks to candle when the display also shows candy 5 ). This suggests that listeners temporarily consider the two objects with similar names as possible targets.…”
Section: Introductionmentioning
confidence: 99%